Shame and disgust in patients with inflammatory skin diseases: a systematic review of psychological correlates and psychotherapeutic approaches - Fink-Lamotte, Jakob; Wehle, Sebastian; Brinkmann, Frederica; Pelzer, Marie; Exner, Cornelia; Stierle, Christian (Frontiers in Medicine, 2025)
IntroductionSkin diseases are among the most common diseases worldwide and can cause severe psychological and social impairments. Negative self-directed emotions like shame and disgust may be important in the development and progression of these diseases, and thus, patients may benefit from psychotherapeutic approaches targeting shame and self-disgust. The first aim of this systematic review is to investigate the existing literature regarding shame and disgust as psychological correlates of inflammatory skin diseases. The second aim is to review the existing literature concerning the evidence of the efficacy of mindfulness-based and compassion-based therapy for alleviating shame and self-disgust in the context of skin diseases.MethodsTherefore, we carried out a systematic literature review via the databases PubMed, Web of Science and PSYINDEX.Results46 manuscripts were included in this review. Research shows that acne vulgaris, psoriasis, and atopic eczema are accompanied by a severe psychosocial burden, shame, and self-disgust, often due to highly visible skin lesions in affected patients. The use of mindfulness-based and compassion-based approaches is already being studied to address the experiences of shame and disgust due to these diseases, and initial promising results indicate that they can be considered beneficial in the holistic therapy of skin diseases.DiscussionThis systematic review shows that skin disorders have a significant psychosocial impact, leading to shame and self-disgust, especially due to the manifestation of visible skin lesions in affected patients. Mindfulness- and compassion-based approaches are currently being studied as potential treatments for the psychosocial impacts of skin diseases, and show promising results in addressing affected patients’ psychological burden.